NOMADIC FEMINISM: FOUR LINES OF FLIGHT - Al Azmeh, Zeina (European Scientific Journal, ESJ, 2014)
Since its first wave in the late nineteenth century, feminism has reached a legitimation crisis the emergence from which is critical for its survival as a political movement. Several subjective figurations have been proposed by feminists and theorists in order to enable a leap beyond the impasses that feminism faces today. In this paper, the subjective figuration of the Nomad is explored as presented by Rosi Braidotti and inspired by poststructuralist theory, in particular the philosophy of Gilles Deleuze. It is suggested that if feminism has been disserved by the second wave’s adoption of rigid masculinist structures, then the fluid ways of nomadic subjectivity provide valuable tools for advancing it. The argument is formulated around the Deleuzian concept of ‘lines of flight’ suggesting four ways in which nomadic theory offers exit lines from significant impasses confronting contemporary feminism. It is suggested that these exist lines carry potential to move the feminist movement beyond its current stasis; beyond postmodernist cynicism; beyond linear, hierarchical and exclusionary phallogocentrism; and most significantly beyond an outdated reactive and dogmatic feminism.